Local delivery of dexamethasone for prevention of neointimal proliferation in a rat model of balloon angioplasty. - Villa, A E (1994)
A periadventitial polymer system is an alternative local drug delivery technique to obtain and maintain high tissue levels of the drug at the site of vascular injury. To determine if local periadventitial delivery of dexamethasone decreases neointimal proliferation after balloon vascular injury, in three groups of Sprague-Dawley rats, 5% dexamethasone, 0.5% dexamethasone, and placebo silicone polymers were implanted around the left common carotid artery after balloon injury. In a fourth group, placebo polymers were implanted without balloon injury. Dexamethasone serum and tissue levels after polymer implantation were significantly higher in the 5% dexamethasone group compared with the 0.5% dexamethasone group. There was no neointima formation in any of the arterial segments covered with placebo polymers for 3 wk, but without balloon injury. In the arterial segments covered by the 5 and 0.5% dexamethasone polymers, there was a 76 and 75% reduction in intima/media ratios, respectively, compared with the placebo group (5% dexamethasone, 0.26 +/- 0.04; 0.5% dexamethasone, 0.27 +/- 0.03; placebo, 1.09 +/- 0.16, respectively; P < 0.0001). These results suggest that: (a) silicone polymers wrapped around the common carotid arteries for 3 wk did not, without balloon injury, stimulate neointimal proliferation in the rat model; (b) the activity of the drug-eluting polymer for suppressing intimal proliferation was chiefly, but not exclusively, site specific; and (c) transadventitial local delivery of dexamethasone at two different doses markedly inhibits neointimal proliferation after balloon vascular injury.